A survey of the extent of information technology applications among six medical school libraries in Metro Manila - Tantiongco, Roman Gregorio G. 1964-
Except for libraries that are members of the DOST-ESEP library network, the study indicated low levels of automation in most of the respondent institutions, particularly with respect to library information systems.